Fluid flow and heat transfer analysis of TEFC machine end regions using more realistic end-winding geometry - La Rocca, S.; Pickering, S.J.; Eastwick, Carol N.; Gerada, C.; Rönnberg, K. (2018)
In this paper a typical small low voltage TEFC motor (output power ~10 kW) has been studied using computational fluid dynamics. The complexity of the end winding geometries, often consisting of several insulated copper strands bound together, provides a challenge to the modelling and analysis of heat transfer and fluid flow phenomena occurring in the end region which typically is an area of most interest for thermal management. Approximated geometries are usually employed in order to model the end windings to reduce analysis time and cost. This paper presents a comparison of two cases, a typical simplified geometry and a more realistic geometry of end windings and uses these cases to highlight the challenges and impact on predicted heat transfer. A comparison of the two models indicate that the different representations of end winding geometries can affect the heat dissipation rate through the outer housing by up to 45%.